The Micro-Economics Foundations of Islamic Economics - Masudul Alam Choudhury (International Institute of Islamic Thought, 1986)
I. Objective of this Paper The main objective of this paper is to show the relevance of ethical or normative elements in economic theory. The paper builds on the exchange mechanism of economics as the ethical basis of the social order and shows that an ethical economic system must be capable of infdtely reproducing this exchange mechanism in the rational working of the total social system through higher and higher levels of social preferences. In building up this analytical framework of ethical economics, we study the field of social economics in general and of Islamic economics in particular as a field of social economics. Through this we introduce a reconceptualization of ethical economics in terms of the fundamental microeconomic buildmg blocks. The premise of the argument therefore is that since the exchange mechanism is the instrument of transmitting ethical preferences, it is the microeconomic foundation that is capable in the first place of buildmg up the ethical economic order as a whole. The ethical macroeconomic system depends upon aggregations at the microeconomic level. II. Introduction As Boulding mentions, economics first started off as a moral science. Adam Smith, who was ”both the Adam and the Smith of systematic economics,” was professor of moral philosophy. Even long after that, economics continued to be taught as a part of the moral sciences tripos at Cambridge University ...